A new analytical approach for phase-margin specification-based target-loop selection for different class of dead-time processes. (23rd November 2021) - Chakraborty, Sudipta
Target-loop based controller design is one of the most utilised strategies in industry. For such designs, selection of the proper target-loop is the most important task. In this paper, an analytical approach for selection of target-loop for different classes of processes have been presented. Explicit formulas for the target-loop selection have been derived with phase margin specifications. To validate the proposed target-loop, case studies on various process models have been made. Lastly, to check the applicability and superiority, a control comparison with proposed loop based controller and a recently developed one is also included.